TRENDS IN INDIVIDUAL COUNSELING SERVICES: A BIBLIOMETRIC ANALYSIS FROM 1938-2025 - Anami, Ikfina Hida Maula; Utomo, Dian Purbo (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Individual counseling has experienced significant growth in recent years. However, there is limited research on its research trends globally. This research employs a bibliometric analytic methodology utilizing the PRISMA framework for identification, sorting, filtering, and describes the identification process of articles published in Scopus-indexed journals from 1938 to 2025. The researcher analyzed the data using Openrefine-3.9.3, Biblioshiny R 127.0.0.1:6905, and VOSviewer 1.6.20. Individual counseling, personal counseling, one-on-one counseling, face-to-face counseling, and counseling service were the keywords that were employed. The results show that individual therapy has been steadily increasing, peaking between 2012 and 2024. The largest donation comes from the United States, which Australia and the United Kingdom follow. Ohio State University is the affiliation that produces the most publications, and Iowa State University has the highest number of citations. The findings also show that the dominant themes in the publications are